Decreased serum testosterone level was not significantly correlated with lipid indices in elderly men - Neda Meftah; Ali Bijani; Seyed reza Hosseini; Amirmorteza Soleymani (Babol University of Medical Sciences, 2021)
Background: Aging in men causes a gradual decline in endogenous testosterone levels, which may have detrimental effects on their health status. Testosterone deficiency is thought to promote atherosclerosis by modulating lipid metabolism. Therefore, this study was conducted to evaluate the serum testosterone level and its correlation with lipid profile in men aged ≥60 years old. Methods: All elderly men aged ≥60, residing in Amirkola and participating in a phase of the comprehensive project on "investigating the health status of the elderly in Amirkola" were entered into this descriptive cross-sectional study. After fasting over 12 hours, the venous blood samples were taken. Serum concentration of testosterone was determined using ELISA method. Moreover, HDL-LDL, total cholesterol, triglyceride and fasting blood glucose were measured. Results: The prevalence of hypogonadism was 91.28% among the 792 participants of this study with a cut-off point of 9.72 nmol/L (95% confidence interval, 93.25-89.31) and the prevalence of severe hypogonadism with a cut-off point of 5.2 nmol/L was reported 71.59% (95% confidence interval, 74.73-68.44%). Based on the results, there was no significant statistical correlation between the serum level of testosterone and triglyceride (r=0.03, P=0.34). Furthermore, there was a negative correlation between testosterone and HDL, which was not statistically significant(r=-0.05, P=0.13). No significant statistical correlation was found between testosterone and LDL (P=0.98). There was a negative correlation between testosterone and cholesterol, which was not statistically significant (r=-0.02, P=0.49). Conclusion: According to the study results, 91% of men aged ≥60 years old had hypogonadism, no correlation was found between testosterone and lipid indices.